Involvement of ILR4α and TLR4 in miscarriages. (February 2019) - Kolben, Theresa Maria; Rogatsch, Elisabeth; Hester, Anna; Kuhn, Christina; Schmoeckel, Elisa; Czogalla, Bastian; Mahner, Sven; Jeschke, Udo; Kolben, Thomas
Highlights: IL4Rα is expressed in trophoblast cells in healthy pregnancies, spontaneous miscarriages (SM) and recurrent miscarriages (RM). IL4Rα is downregulated in the syncytiotrophoblast of SM and of RM. TLR4 is expressed in trophoblast cells in healthy pregnancies, SM, and RM. The intermediate villous trophoblast showed a lower expression of TLR4 in SM. Abstract: Background: The purpose of this study was to analyze the involvement of signaling via Interleukin-4-Receptor α (IL4Rα) and Toll like receptor (TLR) 4 at the fetomaternal interface in the process of early pregnancy. Patients And Methods: Placenta specimens of 46 patients in early pregnancy were analyzed (normal pregnancy (n = 15), spontaneous (n = 15) and habitual abortion (n = 16)). TLR4 and IL4Rα were analyzed by immunohistochemistry, immunofluorescence and real time PCR. Statistical analysis was carried out using SPSS 23 and Microsoft Excel. Results: IL4Rα could be detected in trophoblast cells of all groups. It was significantly downregulated in the syncytiotrophoblast of spontaneous and recurrent abortions (p = 0.001), and in decidual tissue of spontaneous abortions (p = 0.001). Expression of TLR4 was decreased in the intermediate villous trophoblast (IVT) and decidua of spontaneous abortions (p = 0.04 & 0.003, respectively). On mRNA level expression of IL4Rα and TLR4 was significantly decreased in the group of recurrent miscarriages (IL4Rα p = 0.002, TLR4 p = 0.004). Conclusion: This study contributes new findings to the understanding of the complex molecular interplay at the fetomaternal interface in normal pregnancy and miscarriages. For the first time signaling via IL4Rα being involved at the very beginning of the generation of new life could demonstrated. Moreover, new evidence was provided regarding TLR4 playing a pivotal role in early pregnancy.